2015
DOI: 10.1590/0100-2945-097/14
|View full text |Cite
|
Sign up to set email alerts
|

Exigência Térmica De Duas Seleções E Quatro Cultivares De Morangueiro Cultivado No Planalto Catarinense

Abstract: HEAT REQUIREMENT OF TWO SELECTIONS AND FOUR STRAWBERRY CULTIVARS GROWN IN THE CATARINENSE PLATEAUABSTRACT -the objective of this study was to estimate the thermal accumulation and phyllochron of four cultivars and two selections of strawberry in the Southern Brazil. the research was carried out in the experimental field at the Centro de Ciências Agroveterinárias, in the University of Santa Catarina, Lages, SC. It was used two advanced knowledge selection of strawberry, called 'Sel1' and 'Sel2', with plants fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 8 publications
0
21
1
1
Order By: Relevance
“…In other studies, the Albion cultivar also had a lower rate of leaf emission when compared to other cultivars, as observed by Mendonça et al, (2012), in a study in which this cultivar required higher accumulation of degree days to emit a leaf. Tazzo et al, (2015) found phyllochron values of 135.61° C day leaf -1 for the Albion cultivar, which is higher than what was seen for Camarosa. For the Albion cultivar, Costa et al, (2012) observed differences in phyllochron of vernalized and non-vernalized seedlings and the appearance of leaves on vernalized seedlings was 93.30° C day leaf -1 , while for nonvernalized seedlings, the phyllochron was 117.80° C day leaf -1 .…”
Section: Variable Phyllochroncontrasting
confidence: 61%
See 1 more Smart Citation
“…In other studies, the Albion cultivar also had a lower rate of leaf emission when compared to other cultivars, as observed by Mendonça et al, (2012), in a study in which this cultivar required higher accumulation of degree days to emit a leaf. Tazzo et al, (2015) found phyllochron values of 135.61° C day leaf -1 for the Albion cultivar, which is higher than what was seen for Camarosa. For the Albion cultivar, Costa et al, (2012) observed differences in phyllochron of vernalized and non-vernalized seedlings and the appearance of leaves on vernalized seedlings was 93.30° C day leaf -1 , while for nonvernalized seedlings, the phyllochron was 117.80° C day leaf -1 .…”
Section: Variable Phyllochroncontrasting
confidence: 61%
“…For the Camarosa cultivar, which showed lower phyllochron, a greater amount of leaves (16 leaves) was observed as compared to Albion (10 leaves), from this morphological characteristic it can be inferred that Camarosa has a greater leaf area, unlike Albion which demonstrated a lesser rate for the transformation of photosynthetic energy and consequently a lesser accumulation of reserves (Tazzo et al, 2015), factors which can influence crop yields.…”
Section: Variable Phyllochronmentioning
confidence: 88%
“…is a herbaceous and creeping plant, which although has characteristics of perennial crop, it is cultivated as annual (CALVETE et al, 2008). Its fruit has great economic importance, being the most popular, cultivated and consumed in the small fruit group (TAZZO et al, 2015). In Brazil, the crop is widespread in temperate and subtropical regions, where strawberries are produced for in natura consumption and also for industrialization (RADMANN et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These changes can be related to the development of the seedling that needs some hours of cold to accumulate carbon in its crown and to change stage (TAZZO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%